2005
DOI: 10.1148/radiol.2373041439
|View full text |Cite
|
Sign up to set email alerts
|

Personal Computer versus Workstation Display: Observer Performance in Detection of Wrist Fractures on Digital Radiographs

Abstract: The results of this study showed that there was no difference in accuracy of observer performance for detection of wrist fractures with a PC compared with that with a PACS workstation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 15 publications
4
24
0
Order By: Relevance
“…Our findings are in accordance with several studies that have shown similar performances for color and monochrome displays in a variety of clinical tasks such as brain CT, 5 radiography of wrist fractures, 6,7 computed radiographs of the hands in early rheumatoid arthritis, 8 and chest radiographs in interstitial lung disease. 9 In another study, Goo et al 10 found that for chest radiographs, a display luminance as low as 86 cd/m 2 was acceptable provided that the ambient illuminance was low.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are in accordance with several studies that have shown similar performances for color and monochrome displays in a variety of clinical tasks such as brain CT, 5 radiography of wrist fractures, 6,7 computed radiographs of the hands in early rheumatoid arthritis, 8 and chest radiographs in interstitial lung disease. 9 In another study, Goo et al 10 found that for chest radiographs, a display luminance as low as 86 cd/m 2 was acceptable provided that the ambient illuminance was low.…”
Section: Discussionsupporting
confidence: 92%
“…Doyle et al 13 found that there was no difference in the accuracy of observer performance for detection of wrist fractures with a personal computer monitor compared with that of a picture archiving and communication system workstation. Geijer et al 9 did not find any significant difference in image quality between a medical grade monochrome LCD display and a colour LCD display of equal spatial resolution, with either a contrast-detail phantom or a VGA.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed there was no difference in accuracy of observer performance for detection of wrist fractures with a PC (color monitor 1024 Â 768) compared with a PACS workstation monitor. 5 A similarly designed study showed a nonstatistically significant (at 95%) trend toward higher diagnostic accuracy using a dedicated medical grade monitor vs. 2 megapixel (MP) 20 in. LCD monitor when evaluating thoracic radiographs for pneumothorax and wrist fractures.…”
Section: Dual Function Worktationsmentioning
confidence: 99%